ChemInform Abstract: An Efficient Synthesis of 1‐Amidoalkyl‐2‐naphthols Catalyzed by Zinc Oxide Nanoparticles under Solvent‐Free Conditions. Issue 32 (22nd July 2016) - Singh, Rajesh K.; Bala, Renu; Kumar, Sahil
Abstract: The one‐pot condensation of aromatic aldehydes, naphthol, and amides under microwave irradiation affords the title compounds.